O necessário (re) pensar do direito ambiental atual frente aos desastres naturais e eventos extremos - Galvão, Rosa Maria Duarte (Universidade do Vale do Rio dos Sinos, 2015)
The present study aims to structure the description and rethink environmental natural disasters and global risks posed by climate change, under Environmental Law. The contemporary society, as a creator of abstract and global risks, instigates reflection on a new paradigm of global ecological issue given the requirement of a new position regarding social systems - specifically legal and political systems. Thus, through his Theory of Autopoietic Systems, Niklas Luhmann held up the theoretical foundation about society in the development of this research. Besides that, the risks arising from environment cause exasperation in social systems, which produce resonances both in systems themselves as well as in other social systems. Environmental disasters have always existed - and will probably continue to happen wherever there is a causal link with climate extremes. The understanding, assimilation and fact management require interdisciplinary knowledge, whose striking feature is the uncertainty of its likelihood. Furthermore, they are systemic, both in reasons - economic, social, and political – as well as in consequences, and quite often lead to disasters. Therefore, Environmental Law is a response to the (self) exasperation produced by social systems, for which Classic Law can no longer provide the appropriate answers society needs. In this context disasters should be seen as political, social and legal opportunities of supplanting disregard to the limits of nature, and a construction of rationality and environmental sustainability, for which not only the States have the mission to protect the environment, but also the whole society, ensuring use conditions for every human being inhabiting planet Earth.
Keywords: Mudanças climáticas; Desastres naturais; Sociedade de risco; Sistêmico; Transdisciplinariedade; Climate change; Natural disasters; Risk society; Systemic; Transdisciplinarity; ACCNPQ::Ciências Sociais Aplicadas::Direito